Pengaruh Service Quality terhadap Customer Satisfaction pada Aplikasi Tokopedia - Maya Irjayanti; netia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
As technology advances, human activities become easier, including shopping. E-commerce is now the main choice for many people to shop online comfortably and efficiently. Tokopedia is one of the leading e-commerce platforms in Indonesia with the highest number of monthly web visits. However, there are still many complaints regarding service quality which can affect user satisfaction and application rankings on the App Store and Play Store. This research measures the influence of service quality on customer satisfaction by focusing on the aspects of convenience, reliability, ease of use, fulfillment and security. The research method used was quantitative with non-probability sampling on 155 Tokopedia user respondents who had a history of purchase transactions. Data was collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results show that service quality has a positive and significant influence on customer satisfaction. Tokopedia needs to increase transaction security with advanced encryption, improve delivery speed, product quality and service responsiveness. Intuitive interface design and features that make it easier to navigate and use the app are also important. Technical reliability, speed of response and accuracy of service will strengthen customer satisfaction and Tokopedia's position in the e-commerce market.